Environmental effects on great tit life-histories - Wilkin, T; Teddy Wilkin (2006)
﻿ Explaining variation between individuals is a central concept in ecology. Phenotypic variation is the product of genes, environments and their interactions. In contrast to genotypes which are fixed within individuals, environments vary considerably in time and space and have measurable effects on phenotypic quality between and within individuals. The aim of the current work was to identify environmental sources of life-history variation in a wild population of the great tit. The size of Thiessen polygons formed around c. 8000 nestboxes occupied over a 41 year period was used to estimate breeding density at the level of the individual. Linear mixed modelling showed that birds breeding in large territories laid more eggs and produced heavier fledglings that were more likely to survive to breed, than those in smaller territories. Systematic capping of territory sizes revealed that birds breeding in territories more than 2ha in size were unconstrained by density. This method of measuring individual density identified important relationships between density and life-histories and allowed for the accurate separation of other environmental effects usually confounded by density. For example, the life-histories and breeding density of woodland passerines often both vary with distance from the woodland edge. Using the Thiessen polygons to control for density we were able to independently examine edge effects on life-histories. Results confirmed higher density at edges and independently showed that birds near the woodland edge tended to lay smaller clutches of larger eggs later in the season, than birds away from the edge, probably due differences in habitat quality. A further use of Thiessen polygons was to determine the scale at which to measure oak availability in the vicinity of each occupied nestbox. Birds breeding in oak rich polygons laid larger clutches, earlier in the season and had heavier nestlings than birds in oak poor polygons, independently of density and edge effects. What's more, including oaks in life-history models, reduced or eliminated the effect of the Thiessen polygons, suggesting that density dependent life-histories are to some extent explained by reduced oak availability at high density. Clutch size, fledgling mass and recruitment were also found to correlate with local soil calcium. Analyses performed at several spatial scales found the greatest effect of calcium at scales of c.500m. This figure may indicate the average distance females were travelling to obtain calcium rich food during periods of high demands. That breeding environments strongly affect life-histories has been demonstrated by the above work. However, no correlations were found between natal environment and the subsequent life-histories of recruited individuals, probably due to high mortality in great tits, which favours current condition over any character that conveys benefits later in life. This result shows that long-term effects of rearing environments cannot be assumed as it depends on the life-history conditions under which they are found. The results of this study suggest a pervasive role of fine-scale environment variation in determining the life-histories of individual great tits. Moreover, the study demonstrates the efficacy of GIS to model such variation and applying it to explaining life-history variation in long-term databases.